Provider, Caregiver, and Patient Experiences of an Integrated Care Program for Older Adults Designated as Alternate Level of Care: A Qualitative Case Study - Adora Chui; Kimia Sedig; Katie N. Dainty; on behalf of the NYCARES Design Team (International Journal of Integrated Care)
Introduction: Following hospitalization, older adults with complex health and social care needs are often deemed to need an “alternate level of care” (ALC) where care needs are misaligned with resources. Coordinated networks can implement integrated care programs for this group in home settings. Understanding the experiences of providers, caregivers, and patients will inform ongoing implementation efforts. Methods: A qualitative case study was undertaken of North York Community Access to Resources Enabling Support (NYCARES), a novel integrated care program implemented during the COVID-19 pandemic. Data collection consisted of semi-structured interviews, document analysis, and observational field notes; data were thematically analyzed. Results: Thirty-six providers, caregivers, and patients were interviewed. Three themes were developed: 1) NYCARES as a lifeline; 2) Experiences tempered by expectations and connection; and 3) The role of integrated care. Discussion: The NYCARES program was seen as valuable, but implementation posed challenges for each participant group due to varying expectations and perceived degree of connection between patients, families, and providers. Conclusions: The local coordinated network successfully implemented the NYCARES program for ALC patients despite challenges in stakeholder connections. Similar programs should formally support caregivers and forefront multidirectional communication, particularly between providers in different implementation roles.